2018
DOI: 10.1371/journal.pone.0199689
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA methylation prognostic signature of acute myelocytic leukemia

Abstract: BackgroundThe aim of this study is to find the potential survival related DNA methylation signature capable of predicting survival time for acute myelocytic leukemia (AML) patients.MethodsDNA methylation data were downloaded. DNA methylation signature was identified in the training group, and subsequently validated in an independent validation group. The overall survival of DNA methylation signature was performed. Functional analysis was used to explore the function of corresponding genes of DNA methylation si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…4). Among the dysregulated FOXK1/K2 targets by mutant ASXL1 are multiple tumor suppressors: VHL mutations and promoter hypermethylation play a crucial role in the development of AML (Labno-Kirszniok et al, 2013;Gossage et al, 2015;Moura et al, 2018); SOCS1 and SOCS2 are associated with dysregulation of cell growth, cancer-associated inflammation, and cell death induced by multiple cytokines and hormones (Duncan et al, 2017;Jiang et al, 2017); TXNIP plays an important role in glucose uptake and redox homeostasis (Waldhart et al, 2017). Phenotypically, mutant ASXL1 impairs the BAP1-ASXL1-FOXK1/K2 transcriptional nexus and downregulates TXNIP, VHL, and SOCS1/2, and consequently promotes glucose metabolism and enhances oncogenic HIF-1α and JAK-STAT3 signaling pathways known to be altered in hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Among the dysregulated FOXK1/K2 targets by mutant ASXL1 are multiple tumor suppressors: VHL mutations and promoter hypermethylation play a crucial role in the development of AML (Labno-Kirszniok et al, 2013;Gossage et al, 2015;Moura et al, 2018); SOCS1 and SOCS2 are associated with dysregulation of cell growth, cancer-associated inflammation, and cell death induced by multiple cytokines and hormones (Duncan et al, 2017;Jiang et al, 2017); TXNIP plays an important role in glucose uptake and redox homeostasis (Waldhart et al, 2017). Phenotypically, mutant ASXL1 impairs the BAP1-ASXL1-FOXK1/K2 transcriptional nexus and downregulates TXNIP, VHL, and SOCS1/2, and consequently promotes glucose metabolism and enhances oncogenic HIF-1α and JAK-STAT3 signaling pathways known to be altered in hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have established the oncogenic roles of VHL/HIF-1α and SOCS/JAK-STAT pathways in regulating leukemia cell growth and hematological malignancies (Labno-Kirszniok et al, 2013;Moura et al, 2018). We found that C-terminally truncated ASXL1 mutant mildly increased the cellular susceptibility to STAT3 inhibitor, with the IC 50 for C188-9 being 7.9 ± 0.72 μmol/L and 11.84 ± 1.31 μmol/L in ASXL1 +/N590 and ASXL1 +/− cells, respectively (Fig.…”
Section: Tumor-derived Asxl1 Mutants Promote Leukemia Cell Growth Thrmentioning
confidence: 99%
“…GABBR1 has been introduced as a survival associated marker for AML 32 . Excessive signal transduction through GABBR1 triggers growth and migration of cancer cells 32 . These ndings support our data showing the association of increased expression of GABBR1 and chemoresistance in AML samples.…”
Section: Discussionmentioning
confidence: 99%
“…6b) 31 . GABBR1 has been introduced as a survival associated marker for AML 32 . Excessive signal transduction through GABBR1 triggers growth and migration of cancer cells 32 .…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation changes in the peripheral blood have been considered to have great potential as a source of locus-specific biomarkers that can be used for the early detection and monitoring of environmental pollution [6, 7]. This promise is considerable and has been fulfilled by the use of alterations of DNA methylation in populations exposed to pollutants such as cadmium[8], and polycyclic aromatic hydrocarbon[9]; however, a new and more reliable, repaid and sensitive method for promoter methylation analyses in clinical samples is needed.…”
Section: Introductionmentioning
confidence: 99%